A Multiscale Approach to Blast Neurotrauma Modeling: Part I – Development of Novel Test Devices for in vivo and in vitro Blast Injury Models - Panzer, Matthew B.; Matthews, Kyle A.; Yu, Allen W.; Morrison, Barclay; Meaney, David F.; Bass, Cameron R. (Frontiers in Neurology, 2012)
The loading conditions used in some current in vivo and in vitro blast-induced neurotrauma models may not be representative of real-world blast conditions. To address these limitations, we developed a compressed-gas driven shock tube with different driven lengths that can generate Friedlander-type blasts. The shock tube can generate overpressures up to 650 kPa with durations between 0.3 and 1.1 ms using compressed helium driver gas, and peak overpressures up to 450 kPa with durations between 0.6 and 3 ms using compressed nitrogen. This device is used for short duration blast overpressure loading for small animal in vivo injury models, and contrasts the more frequently used long duration/high impulse blast overpressures in the literature. We also developed a new apparatus that is used with the shock tube to recreate the in vivo intracranial overpressure response for loading in vitro culture preparations. The receiver device surrounds the culture with materials of similar impedance to facilitate the propagation of a single overpressure pulse through the tissue. This method prevents pressure waves reflecting off the tissue that can cause unrealistic deformation and injury. The receiver performance was characterized using the longest helium-driven shock tube, and produced in-fluid overpressures up to 1500 kPa at the location where a culture would be placed. This response was well correlated with the overpressure conditions from the shock tube (R2 = 0.97). Finite element models of the shock tube and receiver were developed and validated to better elucidate the mechanics of this methodology. A demonstration exposing a culture to the loading conditions created by this system suggest tissue strains less than 5% for all pressure levels simulated, which was well below functional deficit thresholds for strain rates less than 50 s-1. This novel system is not limited to a specific type of culture model and can be modified to reproduce more complex pressure pulses.